Statistical approach for interpretation of power transformers frequency response analysis results. Issue 3 (1st May 2015) - Behjat, Vahid; Mahvi, Mojtaba
Abstract : In spite of many research efforts on fault diagnosis using frequency response analysis (FRA) method, there is still no universally accepted and systematic interpretation technique for these tests and 'expert opinion' is often sought when any damaging trend is observed as a result of fault occurrence. This study deals with statistical criteria for interpretation of the FRA results and presents a number of statistical and mathematical indicators that have not been used so far. A measurement setup accompanied by a transformer as a test object, on which winding faults are imposed, completes the test setup for performing the FRA measurements. The parameters are applied to the experimental FRA measurements and the results are compared by a simple normalising equation. Finally, the indicators which are adding more objectivity and transparency to interpretation of the FRA results are presented. Sweep frequency response analysis (SFRA) method is used in this study because of its efficiency and simplicity. It was found through this research work that F ‐test, which introduced in this study for the first time, has higher sensitivity, and the differences between the normal and faulty responses of the transformers' windings is more reflected in this parameter compared with the other ones.